2009
DOI: 10.1002/sia.3011
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristic of self‐assembled corrole dimers on HOPG

Abstract: Our study first focus on two types of corrole dimers oxidized and reduced forms on highly oriented pyrolytic graphite (HOPG) surface. Scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS) and contact angle measurement (CAM) were used to investigate the self-assembled monolayers of corrole dimers adsorbed on HOPG surfaces at room temperature in air. XPS and CAM results have confirmed both two molecules adsorbed on an HOPG surface and formed self-assembled films, and STM experiments found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This is possible only for flatly adsorbed and isolated or at most partially overlapping molecules. Such an orientation is virtually universal for phthalocyanines, porphyrins and corroles adsorbed on a vast variety of substrates including metallic [71][72][73][74], semi-conducting [75], and non-conductive [76] materials, but most of all on graphitic surfaces [77][78][79][80][81][82], where strong attractive dispersion interactions exist between the delocalized π-electron clouds of the adsorbates and the surface. Due to the flat orientation of the (hydrophobic) adsorbed catalytic molecules on the hydrophobic surface, neither the surface hydrophobicity nor its morphology is significantly affected by the adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…This is possible only for flatly adsorbed and isolated or at most partially overlapping molecules. Such an orientation is virtually universal for phthalocyanines, porphyrins and corroles adsorbed on a vast variety of substrates including metallic [71][72][73][74], semi-conducting [75], and non-conductive [76] materials, but most of all on graphitic surfaces [77][78][79][80][81][82], where strong attractive dispersion interactions exist between the delocalized π-electron clouds of the adsorbates and the surface. Due to the flat orientation of the (hydrophobic) adsorbed catalytic molecules on the hydrophobic surface, neither the surface hydrophobicity nor its morphology is significantly affected by the adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated FeTPC molecules on Cu (1 1 1) were studied by STM and conformational manipulation was conducted with the STM tip [170]. Corrole dimers were studied by Miao et al on HOPG [441], Au(1 1 1) and mica [442] after preparation by dropcasting under ambient conditions. 4.2.1.…”
Section: Tetrapyridylporphyrinsmentioning
confidence: 99%
“…366 Miao et al reported the formation of self-aggregates of corroles dimers on surfaces such as highly ordered pyrolytic graphite (HOPG), mica, and Au. 367,368 Hameren et al reported the self-aggregation of corroles trimers in n -hexane solution. 369,370 To date, characterization of the aggregates of sugar-coated corroles or sugar-coated corrolazines is not reported.…”
Section: Nanoaggregates Of Sugar-substituted Porphyrinoids and Relmentioning
confidence: 99%